Satisfaction and organizational commitment in job performance: A systematic review - Tarmeño-Bernuy, Luis Edgar; Cosme-Silva, Omar; Rincón-Calvo, Sauri Yesenia (Edelweiss Applied Science and Technology, 2025)
Present a biometric analysis of satisfaction and commitment in relation to job performance. A hermeneutic methodology of the variables: satisfaction, commitment, and performance. Regarding the first variable, it focuses on the “attitude” of the collaborator towards their own work, “recognition,” and “ideal conditions” to develop their tasks; in reference to organizational commitment, it is conceptualized from “individual identification,” characterized by the implication in favor of the organization and belief in it, “involvement,” and “sense of belonging”; and the third variable, teaching performance, is related to “fulfillment” when assuming responsibility and developing it according to the proposed indicators. From the bibliographic review, it is determined that institutions carry out actions in favor of providing quality service, considering all the factors that may impact its development. For that reason, the senior management of organizations concentrates their efforts on meeting the needs of their staff and facing atypical situations that the environment presents, improving the attitude of collaborators, recognizing their tasks, and providing a safe environment, whether in person or remotely. This study is essential for organizations, as it identifies the relationship between satisfaction and work commitment, elements that directly impact employee performance. By understanding these dynamics, institutions can implement effective strategies that improve staff well-being, thus optimizing their productivity and retention. The value of this study lies in its contribution to understanding how satisfaction and organizational commitment influence job performance. It provides a theoretical and practical framework that allows organizations to identify areas for improvement in talent management.